Natural attenuation processes for remediation of arsenic contaminated soils and groundwater - Wang, Suiling; Mulligan, Catherine N. (Journal of hazardous materials, 2006)
Arsenic (As) contamination presents a hazard in many countries. Natural attenuation (NA) of As-contaminated soils and groundwater may be a cost-effective in situ remedial option. It relies on the site intrinsic assimilative capacity and allows in-place cleanup. Sorption to solid phases is the principal mechanism immobilizing As in soils and removing it from groundwater. Hydroxides of iron, aluminum and manganese, clay and sulfide minerals, and natural organic matter are commonly associated with soils and aquifer sediments, and have been shown to be significant As adsorbents. The extent of sorption is influenced by As speciation and the site geochemical conditions such as pH, redox potential, and the co-occurring ions. Microbial activity may catalyze the transformation of As species, or mediate redox reactions thus influencing As mobility. Plants that are capable of hyperaccumulating As may translocate As from contaminated soils and groundwater to their tissues, providing the basis for phytoremediation. However, NA is subject to hydrological changes and may take substantial periods of time, thus requiring long-term monitoring. The current understanding of As NA processes remains limited. Sufficient site characterization is critical to the success of NA. Further research is required to develop conceptual and mathematical models to predict the fate and transport of As and to evaluate the site NA capacity. Engineering enhanced NA using environmentally benign products may be an effective alternative.